The Effect of Organizational Culture Mediated with Working Motivation towards the Economics Teacher of Islamic Senior High School in Kudus Regency - Marinda, Aryanti; Yulianto, Arief; Widiyanto, Widiyanto (Universitas Negeri Semarang, 2019)
The performance of Human Resources becomes the spearhead of organization in achieving the goal of its working programs. The organization attempts to improve the performance of Human Resources to achieve its vision and mission. The high performance of Human Resources is able to make the organization go concern and competition in providing its service. The performance of Human Resources still becomes a problem which is faced by the school (Islamic Senior High School). A good performance of teachers is one of organization’s targets in achieving high working productivity. This research aims to examine and analyze empirically the effect of organizational culture through working motivation towards the Economics teacher’s performance of Islamic Senior High School in Kudus Regency. The method of this research uses quantitative approach and field research type. The population is 50 Economics teachers in Kudus Regency with census sample. The data collection techniques of this research are documentation and questionnaire. The data analysis techniques are multiple regression test and path analysis. The result of regression test shows that organizational culture and working motivation have positive significant effect partially towards the performance of Economics teachers. The organizational culture and working motivation have positive significant effect simultaneously towards the performance of Economics teachers. The path analysis test reveals the big effect of organizational culture does not directly affect teacher’s performance through working motivation of 29,6% which is proven by total effect > dirrect effect = (0,562 > 0,336) meaning that there is a positive effect of organizational culture towards the performance of Economics teachers of Islamic Senior High School over Kudus Regency through working motivation. Working motivation will be more strengthening the organizational culture in achieving the performance of Economics teachers.